Determination of Professional Competence Level Criteria - Svetlana Ivashnova (Pedagogical Discourse, 2013)
In the article presents the results of study of different models of professional competence of pedagogical workers, empiric research of indexes and descriptors that are used in the process of attestation of pedagogical workers; the author’s system of indexes and descriptors, based on the B.Bloom’s taxonomy is offered.